Niematerialne aspekty biedy odzwierciedlone w polskiej leksyce i frazeologii - Ewa Młynarczyk (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica)
The paper is another contribution to research on the image of material deprivation, which is preserved in the Polish language. The material basis consists of fixed phrases relating to material deprivation seen from the panchronic perspective, which have been excerpted from phraseo- and paremiographic collections and dictionaries of the Polish language. The analysis of the material was carried out in the spirit of the Lublin school of cultural linguistics, and its purpose is the reconstruction of the elements that constitute the linguistic image of poverty in aspects which are non-material. The analysis of the collected material has demonstrated that in Polish phraseological and paremic resources, as well as in the semantic development of some words, an image of interpersonal relationships connected with poverty has been preserved: lack of respect, negligence and contempt, which are experienced by the poor in their relationships with the better-off ones, including family and friends; inappropriate treatment in legal terms, unfair allocation of goods, limited access to social promotion for people who come from impoverished families, or the need to hide one’s own situation. This contemptuous treatment of the poor is also manifested in some ways of calling such people and the whole communities. The phenomena that the phrasemes refer to are described in contemporary journalism and scientific studies.